Сучасний стан і особливості соціально-відповідального маркетингу в Україні - Васильєва, М. В. (Ways to Improve Construction Efficiency, 2014)
This article is about “social-responsible marketing “ and the main aspects of the concept of social-responsible marketing and its importance to the company. Analyzes the key features of the implementation of social-responsible marketing in companies and enterprises of Ukraine.